A unicellular relative links aggregative multicellularity to animal origins - Ruibao Li; Jennah E. Dharamshi; Kyle Kwok; Iñaki Ruiz-Trillo; Joseph P. Gerdt (Nature, 2026)
Abstract How animals evolved complex multicellularity from their unicellular ancestors remains unanswered. Unicellular relatives of animals exhibit simple multicellularity through clonal division, formation of multinucleate coenocytes or aggregation 1 . Animal multicellularity may therefore have evolved from one (or a combination) of these behaviours. Aggregation has classically been dismissed as a means to complex multicellularity 2 . However, aggregation occurs in many extant animal cells and has also been recently described in three close unicellular relatives of animals (the choanoflagellates Salpingoeca rosetta and Choanoeca flexa , and the filasterean Capsaspora owczarzaki ) 3–5 . It is unclear whether aggregation in these species is derived or ancestral, and its relevance for animal origins remains unclear. Here, to fill this gap, we investigated whether an additional close unicellular relative of animals can undergo aggregation. We found that the marine free-living bacterivorous filasterean Ministeria vibrans 6 forms homogeneous aggregates with reproducible kinetics that have long-term stability, and that improved feeding and mating may be evolutionary drivers of this aggregation. Notably, we found that homologues of many animal multicellularity genes involved in cell adhesion, signalling and transcriptional regulation were deployed during the aggregation process, indicating that they may have been used for aggregation in the unicellular ancestors of animals before being co-opted into animal multicellular development. Thus, our results are consistent with aggregative multicellularity being key to the evolution of the multicellular animal genetic toolkit.